Caspase-3 activity in papillary thyroid carcinomas - Mishunina, T.M.; Kalinichenko, O.V.; Tronko, M.D.; Statsenko, O.A. (Experimental Oncology, 2010)
The aim of this work was to assess caspase-3 activity in the tissue of papillary thyroid carcinomas of patients and analyze the peculiarities of changes in this activity depending upon a number of pathomorphological and clinical features of tumoral process.